Functional Aspects of the Development of International Tourism - ZVYAGINTSEVA, Elena Petrovna; EPISHEVA, Olga Sergeevna; TSYGANKOVA, Elena Evgenyevna; AZAROVA, Ofeliia Andranikovna; SHELYGOV, Aleksandr Vladimirovich (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
The article is devoted to functional aspects of international tourism development. Substantial lagging in the functional provision of the development of the international tourism market has been established due to such negative aspects as the lack of planned measures, substantial accumulation of tourist flows, absence of relevant security of tourists, incompliance of infrastructure, illegal labor migration, and an increase in the number of force majeure events. All these factors make it necessary to expand a network of travel agencies so that they are able to cooperate with public authorities. It has been proven that international tourism has become a key segment of the modern global market, in the structure of which tourism services play a key role. The impressive scope of international tourism operations has been identified, spanning most countries of the world and drawing close attention to the problems related to the regulation of international tourism services at all levels (national, supranational, and global).